Monitoring and evaluation platform for HEARTS in the Americas: improving population-based hypertension control programs in primary health care. - Prado, Patric; Gamarra, Angelo; Rodriguez, Libardo; Brettler, Jeffrey; Farrell, Margaret; Girola, Maria E.; Malcolm, Taraleen; Martinez, Ramon; Molina, Virginia; Moran, Andrew E.; Neupane, Dinesh; Rosende, Andres; et al. (Pan American Journal of Public Health, 2022)
HEARTS in the Americas is the Pan American Health Organization flagship program to accelerate the reduction of the cardiovascular disease (CVD) burden by improving hypertension control and CVD secondary prevention in primary health care. A monitoring and evaluation (M&E) platform is needed for program implementation, benchmarking, and informing policy-makers. This paper describes the conceptual bases of the HEARTS M&E platform including software design principles, contextualization of data collection modules, data structure, reporting, and visualization. The District Health Information Software 2 (DHIS2) web-based platform was chosen to implement aggregate data entry of CVD outcome, process, and structural risk factor indicators. In addition, PowerBI was chosen for data visualization and dashboarding for the analysis of performance and trends above the health care facility level. The development of this new information platform was focused on primary health care facility data entry, timely data reporting, visualizations, and ultimately active use of data to drive decision-making for equitable program implementation and improved quality of care. Additionally, lessons learnt and programmatic considerations were assessed through the experience of the M&E software development. Building political will and support is essential to developing and deploying a flexible platform in multiple countries which is contextually specific to the needs of various stakeholders and levels of the health care system. The HEARTS M&E platform supports program implementation and reveals structural and managerial limitations and care gaps. The HEARTS M&E platform will be central to monitoring and driving further population-level improvements in CVD and other noncommunicable disease-related health.